Nonreciprocal transmission using a multilayer magneto-optical dispersive material with defect. Issue 10 (2nd July 2020) - Yu, Guanxia; Yang, Huizhou; Fu, Jingjing; Zhang, Xiaomeng; Cao, Ruoyu
Abstract : A one-dimensional nonreciprocal structure comprising two asymmetric multilayers filled with magneto-optical dispersive media and a defect layer is designed. The nonreciprocal optical Tamm states (OTSs) are excited at the interface of the two asymmetric multilayer structure with an opposing external magnetic field. With the excitation of the nonreciprocal OTSs, the numerical results show that the waves can be transmitted and be reflected in one way. These nonreciprocal properties are affected by the layers thickness of the defect layer, the angles of incidence, and the externally applied magnetic fields. Owing to the inherent dispersive property of the magneto-optical media, our investigations show promising potential for the practical application of nonreciprocal structures.